1994
DOI: 10.3109/10428199409073777
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of CD9 Antigen in Acute Lymphoblastic Leukemia

Abstract: A leukemia-associated CD9 glycoprotein antigen released into the extracellular milieu from acute lymphoblastic leukemia cells has been detected using a unique lectin-monoclonal antibody immunoassay. It has been demonstrated that the release of CD9 antigen is an active process and is associated with active cell growth. In addition, the difference of carbohydrate moiety, and hence glycosylation, in the CD9 antigen derived from lymphoblasts and neuroblasts was verified using lectin affinity chromatography. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…Most tetraspanin-specific antibodies would not detect these bands, since they bind at the large extracellular loop. There have been previous reports of shedding of soluble CD9-immunoreactive material into extracellular fluid by certain types of tumor cells [33]. It is not clear whether the CD81 processing that we have observed and this previously reported shedding of CD9 involve similar proteases or cleavage events.…”
Section: Discussioncontrasting
confidence: 43%
“…Most tetraspanin-specific antibodies would not detect these bands, since they bind at the large extracellular loop. There have been previous reports of shedding of soluble CD9-immunoreactive material into extracellular fluid by certain types of tumor cells [33]. It is not clear whether the CD81 processing that we have observed and this previously reported shedding of CD9 involve similar proteases or cleavage events.…”
Section: Discussioncontrasting
confidence: 43%
“…The patients were divided into groups of either superficial (Tis to T1) or invasive (T2 to T4) cancer. The mean age of the patients was 66.8 years (range, 30 mented by imaging and histologic examination. The pathologic staging and grading of bladder carcinoma were performed according to the Japanese general rules for clinical and pathological studies on bladder cancer.'?…”
Section: Patientsmentioning
confidence: 99%
“…8,21,22 shown that CD9 is released by CD9-positive ALL blast and may be related to poor prognosis. 26 Interestingly, the combiAt least one cytogenetic abnormality was identified in 54% of cases.…”
Section: M4mentioning
confidence: 99%